AGAMA DAN KERAGAMAN DALAM FILM INDONESIA DAN MALAYSIA - mufdil tuhri (LP2M IAIN Palangka Raya, 2020)
This article examines the respresentation of religion in two Indonesian and Malaysian films. This article argued that filmmakers have succeeded in trying to portray diversity and religion in the two films. Methodologically, this article compared between two films namely the Indonesian Film, Mencari Hilal (2015) and the Malaysian Film, Wayang (2008). To analyze the film, this article used the theory of Representation by Stuart Hall (1997). This article contend that two films almost showed the same context of polemics between conservative and modernist spectrum of Islam as a dominant religion in two country.